Shaping the Equine Body: Roundtable - Guest, Kristen; Mattfeld, Monica; Raber, Karen; Forrest, Susanna; Nash, Richard; Vaught, Jeannette (Humanimalia, 2023)
This roundtable discussion brings together four prominent scholars from equine studies (Susanna Forrest, Richard Nash, Karen Raber, and Jeannette Vaught) to discuss how we have historically shaped the equine body (and mind) when we breed and train horses, and how taking this history into account might allow us to imagine new ways of living with horses. Three core concerns are addressed from multidisciplinary perspectives: How do human representations, desires, and fantasies inform our interactions with horses? How have equine bodies and minds been shaped by us over time? How do the stories we tell ourselves about equine bodies in turn shape how we relate to horses—and how might we do this differently?